PENGARUH KOMPETENSI GURU TERHADAP MOTIVASI BELAJAR SISWA (STUDI SURVEY SMK DAARUL ULUUM JAKARTA) - Cindy Veronica; Mugiyono (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2024)
ABSTRAK Researchers conducted research based on the results of research data conducted on students at Daarul Uluum Vocational School, Jakarta. The problem in this research is what is competence Teachers have a significant influence on students learning motivation at Daarul Uluum Vocational School, Jakarta. The ai m of this research is to find out the influence of teacher competence on students learning motivation. Teacher competency must be owned and applied by teachers This study uses a quantitative approach. The sample in this research was 31 students, analyzed using the product moment correlation technique. The results of this research show that Teacher Competence has an influence on Student Learning Motivation. Based on the results of product moment analysis calculations, it is obtained that